Determinants of the interest of digital wallet among the accounting students - Nandya Putri Pratiwi; Rita Wijayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study analyzes the factors that influence accounting students' interest in using digital wallets. The research adopts a quantitative approach, using survey data collected through questionnaires and analyzed with statistical methods, including multiple regression analysis in SPSS 21 and Microsoft Excel 2016. The independent variables studied include ease of use, perceived usefulness, and perceived risk, while the dependent variable is students' interest. The study found that all three factors significantly affect students' interest in digital wallets, with strong statistical evidence supporting the rejection of the null hypotheses. However, the study is limited by its small sample size and focus on a specific cohort of accounting students, which affects the generalizability of the results. Future research should explore additional variables and include a more diverse sample of students. Moreover, it is recommended that students enhance their understanding of digital wallets to better optimize their use in daily life.